2015
DOI: 10.1021/acs.joc.5b01603
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Chlorination and Bromination of Enamides and Enamines via an Electrostatic Attraction Effect Using (1,1-Diacetoxyiodo)benzene and a Halide Source

Abstract: The direct chlorination and bromination of (E)-enamines and (Z)-enamides to the corresponding (Z)-configurated α-chloroenamines, α-bromoenamines, and α-chloroenamides have been realized using NiCl2·6H2O or tetrabutyl ammonium bromide as a halide source and (1,1-diacetoxyiodo)benzene as an oxidant. The high stereoselective reactions which produce products with only (Z)-configurations can be attributed to the structure of the intermediates, the conformations of which are controlled by the electrostatic attractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Furthermore, dehydrogenative aminohalogenation of alkenes via Pd catalysis was developed by Jiang and co-workers 11 for the synthesis of brominated enamines. Later Li et al 12 developed Nickel or Diacetoxyiodobenzene promoted halogenation of enamines and enamides. However, examples of alkyne aminohalogenation towards halogenated enamines are scarce (Scheme 1a &b).…”
Section: Scheme 1 Aminohalogenation Of Alkynes and Our Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dehydrogenative aminohalogenation of alkenes via Pd catalysis was developed by Jiang and co-workers 11 for the synthesis of brominated enamines. Later Li et al 12 developed Nickel or Diacetoxyiodobenzene promoted halogenation of enamines and enamides. However, examples of alkyne aminohalogenation towards halogenated enamines are scarce (Scheme 1a &b).…”
Section: Scheme 1 Aminohalogenation Of Alkynes and Our Strategymentioning
confidence: 99%
“…Organoiodine(III) compounds are usually used as oxidants and electrophilic reagents where only one ligand of iodine(III) is removed by the substrate or replacement of both ligands with external nucleophile followed by its decomposition into radicals 12,15,16 However, sequential removal of two ligands from the iodine(III) reagent by active C-H bond of substrate and incorporation of iodobenzene into the same substrate would indubitably make the reactions atom economic, but such organic transformations are not much explored. 9 On the other hand, compared with known aminohalogenation of alkynes, this multiple-site functionalization would be of great importance to produce synthetically potential halogenated enamines in a stereoselective manner.…”
Section: Scheme 2 Plausible Conformations Of Intermediates For Sterementioning
confidence: 99%
“…However, it seemed reasonable that we could use the ( E )-α-unsubstituted ( 3 , R 2 = H) analogs as a starting point. It has been reported that similar compounds can be halogenated at the α-postion and then subjected to metal-mediated cross coupling . Consequently, those compounds, with nitrogen-protected as a carbamate ( 3 , R 3 = OR) to facilitate later elaboration, became the focus of our efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dehydrogenative aminohalogenation of alkenes via Pd catalysis was developed by Jiang and co‐workers for the synthesis of brominated enamines. Later Li et al developed Nickel or Diacetoxyiodobenzene promoted halogenation of enamines and enamides. However, examples of alkyne aminohalogenation towards halogenated enamines are scarce (Scheme a and Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…Organoiodine(III) compounds are usually used as oxidants and electrophilic reagents where only one ligand of iodine(III) is removed by the substrate or replacement of both ligands with external nucleophile followed by its decomposition into radicals, , However, sequential removal of two ligands from the iodine(III) reagent by active C–H bond of substrate and incorporation of iodobenzene into the same substrate would indubitably make the reactions atom economic, but such organic transformations are not much explored . On the other hand, compared with known aminohalogenation of alkynes, this multiple‐site functionalization would be of great importance to produce synthetically potential halogenated enamines in a stereoselective manner.…”
Section: Introductionmentioning
confidence: 99%